Harnessing Village Resources for Economic Independence: A Study on Local Entrepreneurship and Skill Development - Adelia Azzahra (Journal of Village Development Innovation, 2024)
Rural communities have untapped economic potential that, if properly leveraged, could promote economic independence and sustainable development. This study aims to identify how village resources—such as agriculture, crafts, and services—can be optimized through local entrepreneurship and skill development to achieve economic self-sufficiency. Using a qualitative approach, data was collected through interviews and observations of a selected rural community, focusing on resource mapping, local entrepreneurship, skill development, and financial access. Results indicate that while resources are available, their utilization is limited by restricted market access, financial constraints, and a lack of advanced skill training. The findings suggest that expanding training programs, introducing low-interest loans, and providing access to broader markets could significantly enhance local entrepreneurial success. These insights contribute to the understanding of rural economic empowerment and offer practical recommendations for policymakers to support village-based economic initiatives. Overall, this research emphasizes the role of resource management and entrepreneurship in fostering sustainable rural development.